1997
DOI: 10.1002/(sici)1096-8652(199711)56:3<183::aid-ajh9>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Severe thrombocytopenia suggesting immunological mechanisms in two cases of vivax malaria

Abstract: Case 1: A 27-year-old woman, referred to our hospital because of relapsing fever after travel to Thailand, was given a diagnosis of vivax malaria. Clinical investigation revealed thrombocytopenia, elevated platelet-associated IgG (PAIgG), and negative antibody against Plasmodium vivax antigen. After antimalarial treatment, the levels of both the platelets and PAIgG returned to normal. Case 2: A 28-year-old Sri Lankan man was admitted to our hospital with a complaint of fever. The patient had thrombocytopenia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 9 publications
(10 reference statements)
3
40
0
2
Order By: Relevance
“…This finding is consistent with previously reported observations from South America and south Asia where P. vivax is endemic [2]. Clinical complications such as disseminated intravascular coagulation (DIC), platelet associated IgG increase (PAIgG), immune thrombocytopaenia purpura (ITP), acute renal failure, pulmonary oedema, splenomegaly, cerebral malaria, and seizures have been reported in P. vivax cases exhibiting profound thrombocytopaenia [1519, 21]. In these cases, bleeding was observed in a few cases, indicating that thrombocytopaenia in P. vivax does not always lead to bleeding complications.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previously reported observations from South America and south Asia where P. vivax is endemic [2]. Clinical complications such as disseminated intravascular coagulation (DIC), platelet associated IgG increase (PAIgG), immune thrombocytopaenia purpura (ITP), acute renal failure, pulmonary oedema, splenomegaly, cerebral malaria, and seizures have been reported in P. vivax cases exhibiting profound thrombocytopaenia [1519, 21]. In these cases, bleeding was observed in a few cases, indicating that thrombocytopaenia in P. vivax does not always lead to bleeding complications.…”
Section: Discussionsupporting
confidence: 91%
“…Various malaria-endemic countries, including Indonesia, Columbia, Kenya, India, and Pakistan, have documented high frequency of thrombocytopaenia in malaria patients [313]. Furthermore, case reports describing clinical manifestations of thrombocytopaenia due to P. vivax have been described indicating the significance of the respective parameter in vivax malaria [1421]. Recent studies have also highlighted the usefulness of thrombocytopaenia as a plausible clinical marker of malaria diagnosis with significant sensitivity, specificity, positive, and negative predictive values [22–24].…”
Section: Introductionmentioning
confidence: 99%
“…One study identified an increased level of platelet-associated antibodies in thrombocytopenic malaria (falciparum) patients [46] as well as in vivax patients [47]. This was supported by a study that showed an association between polymorphisms in FccRIIa, the platelet IgG receptor and disease severity [48].…”
Section: Immune Mechanismsmentioning
confidence: 88%
“…Some studies suggest that the low platelet counts in malaria might be caused by activation [20] and/or apoptosis of platelets [14], thus leading to its removal by the immune system [12], [15]. Nonetheless, it has also been proposed that immune complexes generated by malarial antigen could lead to sequestration of the injured platelets in the spleen followed by phagocytosis by splenic macrophages [16][19].…”
Section: Introductionmentioning
confidence: 99%